Service Agencies Policy and Nurse Motivation as Determinants of Information for Family Patients in Critical Care Unit - Moch. Bahrudin; Sutomo Sutomo; Hadi Purwanto (Health Notions, 2017)
The family is a system, so if one family member is treated in a critical care unit, then the family will experience stress and anxiety, even a crisis. Therefore, nurses should help the family in reducing stress and anxiety, one of which is by providing information. This study aimed to analyze the relationship between service agency policies and nurse motivation with information for patient families in critical care rooms. The subjects of the study were 45 nurses and 45 patient family members selected by total sampling technique. The collected data were analyzed using logistic regression test. The results show that there is a relationship between policy and external motivation with information for the family. Therefore, critical nursing services need to consider family conditions, so that family stress and anxiety can be lowered. Keywords: Policy, Nurse motivation, Information for family